2007
DOI: 10.1016/j.eurpsy.2007.01.900
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and bruxist behaviour in the patients with temporomandibular joint disorder

Abstract: Conclusion: Suicidality of breast cancer patients is associated with QOL domains but not with clinical characteristics of the illness. Decreasing of faith is associated with suicidality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite being pathological conditions of the temporomandibular complex, incorrect occlusions caused by dental malocclusions and inadequately treated or untreated edentulism are not thought to be the primary causes of TMD (14). A low occurrence of certain malocclusional characteristics (negative overjet, one-sided open bite, one-sided cross bite of men, and edge-to-edge bite of women) with TMD symptoms or signs has been noted by Badel et al (15). In the same study, it was discovered that asymptomatic patients had considerably more hyperbalance and interference contacts than did TMD patients.…”
Section: Occlusal Issuesmentioning
confidence: 96%
“…Despite being pathological conditions of the temporomandibular complex, incorrect occlusions caused by dental malocclusions and inadequately treated or untreated edentulism are not thought to be the primary causes of TMD (14). A low occurrence of certain malocclusional characteristics (negative overjet, one-sided open bite, one-sided cross bite of men, and edge-to-edge bite of women) with TMD symptoms or signs has been noted by Badel et al (15). In the same study, it was discovered that asymptomatic patients had considerably more hyperbalance and interference contacts than did TMD patients.…”
Section: Occlusal Issuesmentioning
confidence: 96%
“…Among the risk factors in this category, attention should be paid to alcohol [63] and tobacco use [64], use of opioids and/or cannabis [65,66], and obesity [67]. Several of these agents may also result in SB [68][69][70][71]. Furthermore, some anticonvulsants that amplify signaling via GABA-A receptors can elicit or exacerbate SA [72].…”
Section: Agents That Can Cause Sleep Apneamentioning
confidence: 99%
“…Bruxism was originally thought to be a central nervous system problem, associated with anxiety, tension, and the release of stressful [4]. Recent studies have shown that bruxism may be caused by a synergistic effect of multiple factors, such as genetic factors [5], neuropsychological factors (long-term anxiety and tension) [6,7], physiological and pathological factors (malocclusion, snoring, sleep disorder) [8][9][10][11], and bad lifestyle habits (smoking, alcoholism, excessive caffeine intake) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%